An Assessment of the Use of Agricultural Marketing Extension among Extension Methods: Insight from Jordan - Altarawneh, Radi; Al-Sharafat , Ali; Altarawneh , Mohammad (Asian Journal of Agriculture and Rural Development, 2020)
This study aimed at assessing the use of agricultural marketing extension services among extension methods provided by public agricultural extension agents in Jordan. A sample survey of public agricultural extension agents was conducted covering the whole Agricultural Directorates in the country. The survey employed a structured questionnaire with pre-coded questions. The entire sample consists of 107 agricultural extension agents. To achieve its goals qualitative as well as quantitative analytical procedures were adopted in this study. A Four point likert-scales was used to compute the respondents overall mean score. The study provided empirical evidence about the lack of agricultural marketing extension among extension methods used by public extension agents in Jordan. Public extension agents in Jordan consider agricultural marketing extension with low priority during their extensive activity. Public agricultural extension activities should be directed to enhance marketing extension activities. Extension methods such as newspapers, radio, TV, mobile, internet and experts systems should be strongly considered to spread marketing knowledge to the farmers. Public agricultural extension activities should be directed to enhance marketing extension activities. Extension methods such as newspapers, radio, TV, mobile, internet and experts systems should be strongly considered to spread marketing knowledge to the farmers.